2016
DOI: 10.1016/j.mehy.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and selective trends in viral acute respiratory tract infections

Abstract: Influenza A and B, and many unrelated viruses including rhinovirus, RSV, adenovirus, metapneumovirus and coronavirus share the same seasonality, since these viral acute respiratory tract infections (vARIs) are much more common in winter than summer. Unfortunately, early investigations that used recycled "pedigree" virus strains seem to have led microbiologists to dismiss the common folk belief that vARIs often follow chilling. Today, incontrovertible evidence shows that ambient temperature dips and host chilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 82 publications
(262 reference statements)
2
74
0
8
Order By: Relevance
“…A different study on this topic has shown that during the epidemic, the risk of increased daily incidence of SARS was 18.18-fold higher in days with a lower air temperature than in days with a higher temperature, in Hong Kong [24] and other regions [25]. Shaw Stewart proposed four mechanisms that could be the main drivers of the seasonality of viral epidemics [26]. He suggested that winter temperatures are associated with increased crowding that might enhance viral transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different study on this topic has shown that during the epidemic, the risk of increased daily incidence of SARS was 18.18-fold higher in days with a lower air temperature than in days with a higher temperature, in Hong Kong [24] and other regions [25]. Shaw Stewart proposed four mechanisms that could be the main drivers of the seasonality of viral epidemics [26]. He suggested that winter temperatures are associated with increased crowding that might enhance viral transmission.…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that winter temperatures are associated with increased crowding that might enhance viral transmission. Furthermore, he suggested that low temperatures can increase the stability of virions outside the body, the host susceptibility, and may activate dormant virions [26].…”
Section: Discussionmentioning
confidence: 99%
“…En un reciente estudio se sugiere que las temperaturas bajas pueden activar los viriones inactivos y, de esta forma, dar inicio al brote epidémico de RSV en la población (24). Este resultado coincide con el resultado de este trabajo en relación con la variable de temperatura mínima.…”
Section: Discussionunclassified
“…Muchmore et al [18] related that Parainfluenza virus types 1 and 3 could be recovered from both asymptomatic and symptomatic subjects throughout winter in an isolated station in the South Pole and concluded that the viruses could not have been introduced and were most probably due to "persistence in man". Shaw-Stewart [19] proposed that the "natural temprrature sensitivity of respiratory viruses" allows virions to become dormant and viral activation as a result of chilling.…”
Section: Herpes Simplex Virus Is Associated With What Is Termed Latenmentioning
confidence: 99%